The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/nano10081474
|View full text |Cite
|
Sign up to set email alerts
|

Green Graphene–Chitosan Sorbent Materials for Mercury Water Remediation

Abstract: The development of new graphene-based nanocomposites able to provide synergistic effects for the adsorption of toxic heavy metals in realistic conditions (environment) is of higher demand for future applications. This work explores the preparation of a green nanocomposite based on the self-assembly of graphene oxide (GO) with chitosan (CH) for the remediation of Hg(II) in different water matrices, including ultrapure and natural waters (tap water, river water, and seawater). Starting at a concentration of 50 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…An additional material employed for marine environmental remediation is the graphene oxide chitosan-based (GO-CH-based). It is a hydrogel with a 3D macrostructure developed taking advantage of the ability of GO to self-assembly in presence of the natural biopolymer such as chitosan [ 141 , 142 ]. Chitosan is a non-toxic and hydrophilic compound deriving from the alkaline deacetylation of chitin, which boosts the adsorption ability of the hydrogel.…”
Section: Enms Employed For Marine Environment Remediation and Theimentioning
confidence: 99%
See 1 more Smart Citation
“…An additional material employed for marine environmental remediation is the graphene oxide chitosan-based (GO-CH-based). It is a hydrogel with a 3D macrostructure developed taking advantage of the ability of GO to self-assembly in presence of the natural biopolymer such as chitosan [ 141 , 142 ]. Chitosan is a non-toxic and hydrophilic compound deriving from the alkaline deacetylation of chitin, which boosts the adsorption ability of the hydrogel.…”
Section: Enms Employed For Marine Environment Remediation and Theimentioning
confidence: 99%
“…Chitosan is a non-toxic and hydrophilic compound deriving from the alkaline deacetylation of chitin, which boosts the adsorption ability of the hydrogel. Nevertheless, GO-CH nanocomposites was not efficient in removing Hg from seawater [ 141 ]. On the other hand, chitosan-grafted carbon nanotubes (CTS-g-CNTs) are gaining more attention as a viable material to remedy contaminated seawater from radioactive Cs.…”
Section: Enms Employed For Marine Environment Remediation and Theimentioning
confidence: 99%
“…"Chitosan nanocomposites," BioResources 16(4), 8525-8566. 8543 Bessa et al (2020) reported Hg (II) removal efficiency (97%) from ultra-pure water with a small mercury dose using CS-GO composite. Simultaneously, using the tap water, river, and seawater, removal efficiency was reduced to about 81%, 13%, and 7%, respectively.…”
Section: Removal Of Heavy Metalsmentioning
confidence: 99%
“…The percentage of removal (R, %) in seawater was 81% after 6 h, which is relevant considering the competition for the surface's chemically active groups and the possible presence of stable mercury chloro-complexes. 12,13 Nevertheless, the GOPEI nanocomposite did not sustain its structure when immersed in water, and after several hours of vigorous magnetic stirring, it disintegrated into very small particulates. This requires the use of time-consuming centrifugation or filtration with a very fine filter to completely remove the GOPEI from the water matrix after treatment, which is not suitable for large-scale water remediation applications.…”
Section: Introductionmentioning
confidence: 99%